The Existence of Ainu Tribe’s Women in Japanese Patriarchal Society (Study of Feminism in Golden Kamuy Anime) - Rahmah, Yuliani (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
Golden Kamuy anime is one attempt by the Japanese government to introduce the Ainu as a minority tribe to young Japanese people. As a literary work popular with the young generation, the story in  Golden Kamuy anime is full of Ainu life and cultural elements. It reflects the existence of the main character of the Ainu tribe’s female named Asirpa. As a representation of Ainu women, the character Asirpa is described as an Ainu woman who is determined to fight for her people. This is an interesting element considering that the Ainu is a tribe that adheres to traditional principles as a patriarchal society which is also a characteristic of Japanese society. By using the research methods of literary sociology and feminist studies as the main theories, this research examines the  Golden Kamuy anime as its material object. The efforts made by the figure Asirpa in the Ainu patriarchal society were analyzed with qualitative research. As a result, it will be known what efforts were made by the character Asirpa to show her existence as a tough woman in her community. Based on the result, the  Golden Kamuy anime story shows that the spirit of feminism can emerge even in traditional societies such as the Ainu tribe